HUBUNGAN PENGETAHUAN, USIA DAN DUKUNGAN SUAMI DENGAN PEMAKAIAN (AKDR) DI PUSKESMAS TELANG JAYA TELANG - Wahiro, Wahiro; Amlah, Amlah; Afrika, Eka (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Contraception is the meeting of a mature egg and sperm cell that results in pregnancy. Contraception is to avoid pregnancy due to the meeting of a mature egg cell with a sperm cell. An estimated 225 million women in developing countries wish to delay or discontinue fertility but do not use any contraceptive method for the following reasons: limited choice of contraceptive method and experience of side effects. Data on the number of active family planning participants in South Sumatra province consisted of IUD 246 people (0.63%), MOW 92 people (0.23%), MOP 116 people (0.29%), condoms 4234 people (10.9%) , Pills 13672 people (35.3%). This research is quantitative using analytical survey research methods, namely correlation analysis research that can be seen how far the contribution of certain factors to the existence of a particular event with the "Cross Sectional" approach. This research was carried out at Telag Jaya Telang Health Center with a sample of 69 respondents. The data used in this research is primary data where this data is obtained through a direct interview process with respondents using a questionnaire tool. The results of the chi-square statistical test for the age variable obtained value = 0.000, knowledge variable obtained value = 0.000, partner support variable was obtained value = 0.000 smaller than = 0.05 indicating there is a significant relationship between age, knowledge and partner support with the use of the IUD in the Telang Jaya Telang Health Center Work Area in 2021 Â KeywordsÂ Â Â Â Â Â Â Â : IUD, Spouse Support, Knowledge, Age